Peran Spiritualitas dalam Pemulihan Kesehatan Mental Generasi Z di Coffee shop Surabaya - Rochalya Wahyu Exflamo; Wiwik Setiyani (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2026)
The advancement of digital technology has exacerbated various mental health challenges for generation Z, including stress, anxiety, academic pressure, and uncertainty about the future. Amidst these conditions, spirituality is viewed as a psychological resource that helps individuals derive meaning from life experiences and strengthens their resilience. This study aims to analyze the role of spirituality in maintaining the mental health of generation Z from the perspective of the psychology of religion, specifically within the context of coffee shop patrons in Surabaya. A qualitative phenomenological approach was employed, utilizing data collection methods such as in-depth interviews, observation, and documentation. The results indicate that spirituality enables generation Z to develop religious coping mechanisms through three primary forms: personal worship practices, self-reflection, and the search for life's meaning. These forms contribute to reduced anxiety, improved emotional regulation, and the development of psychological resilience when facing academic or social pressures. The study’s novelty lies in its analysis of Generation Z's spiritual experiences within a non-formal social setting the (coffee shop) as a context for the formation of religious coping. These findings are expected to serve as a reference for developing mental health services that integrate psychological and spiritual approaches tailored to the characteristics of Generation Z.Keywords - Coping Mechanisms, Generation Z, Mental Health, Psychology of Religion, Spirituality